Investing in the Best Buys : A Review of the Health, Nutrition, and Population Portfolio, FY1993-99 - Claeson, Mariam; Mawji, Tazim; Walker, Christopher (World Bank, Washington, DC, 2013)
This review of the "best buys" in the health, nutrition, and population portfolio, FY93-99, shows that content, as well as process must receive attention in health systems development, in order to achieve increased access to quality health services. The report suggest that significant gains can be made, and measured within lending, by increasing efforts to identify, and invest in the best buys. It describes the Bank's mixed lending for the best buys, ranging from direct support to public health, and clinical services (i.e., investment in disease control programs), to health systems strengthening (i.e., investment in surveillance, and pharmaceutical systems, managerial and technical capacity building) that indirectly support delivery of basic services. Recommendations suggest linking the guidelines of this review to the knowledge management system, and training in basic public health, and Poverty Reduction Strategy work. Moreover, an in-depth review of data at the regional level, could explicitly define options for inclusion of best buys in project implementation, based on case studies that show the role of process, and content in selecting, and setting priorities for best buys.